Tumor-Educated Neutrophils Activate Mesenchymal Stem Cells to Promote Gastric Cancer Growth and Metastasis - Zhang, Jiahui; Ji, Cheng; Li, Wei; Mao, Zheying; Shi, Yinghong; Shi, Hui; Ji, Runbi; Qian, Hui; Xu, Wenrong; Zhang, Xu (Frontiers in Cell and Developmental Biology, 2020)
In response to tumor signals, mesenchymal stem cells (MSCs) are recruited to tumor sites and activated to promote tumor progression. Emerging evidences suggest that in addition to tumor cells, non-tumor cells in tumor microenvironment could also interact with MSCs to regulate their phenotype and function. However, the mechanism for MSCs regulation in gastric cancer has not been fully understood. In this study, we reported that tumor-educated neutrophils induced the transformation of MSCs into CAFs, which in turn remarkably promoted gastric cancer growth and metastasis. Mechanistic study showed that tumor-educated neutrophils exerted their effects by secreting inflammatory factors including IL-17, IL-23 and TNF-α, which triggered the activation of p38 and AKT pathways in MSCs. Pre-treatment with neutralizing antibodies to these inflammatory factors or pathway inhibitors reversed tumor-educated neutrophils-induced transformation of MSCs to CAFs. Taken together, these data suggest that tumor-educated neutrophils promote gastric cancer progression through the regulation of MSCs/CAFs transformation.